Demand-Supply Trends and Projections of Food in India - Surabhi Mittal (Indian Council for Research on International Economic Relations (ICRIER), 2008)
The present paper presents the supply and demand trends of rice, wheat, total cereals, pulses, edible oil/oilseeds and sugar/sugarcane. It provides the demand and supply projections for food items during 2011, 2021 and 2026. These projections have been based on change in productivity levels, changes in price, growth of population and income growth. A comparison with projections provided by other scholars has also been made in the paper. Subsequently, the future supply-demand gap has been discussed in the light of policy requirements. It is concluded that an increase in total demand is mainly due to growth in population and per capita income. A diversification in consumption basket significantly away from cereals has been observed. On the supply side, production is constrained by low yield growths. This is more specific in context of total cereals and sugarcane. While in the short and medium term, there might be surplus of cereals in the country, these prospects are likely to diminish in the years to come. This situation is even more alarming for edible oil, sugarcane and pulses. To meet the future food requirements, the country shall have to either increase agricultural production, or depend on imports. In this light, the paper suggests that the policy focus needs to be laid, towards productivity enhancement in agriculture, through public investment in irrigation, development of roads, research and extension.
Keywords: Q11; Q18; 330; Demand; Projection; Supply; Projection; India; Food; Ernährungssicherung; Gesamtwirtschaftliche Nachfrage; Bruttoinlandsprodukt; Agrarprodukt; Prognose; Indien